MORPHOMETRIC STUDY OF SELECTED ACRIDIDAE EGG PODS UNDER LABORATORY CONDITION - VETHSELO DOULO; NEIKIELIE-Ü NOEMI SOTE (The Bioscan, 2024)
Under lab-based farming, three species namely Oxya velox, Hygracris palutris and Choreodocus robustus of Acrididae was reared to study their eggs and egg pods. The study comprehends about the species availability and its occurrence in both lab and natural condition. Results of morphometric analysis of eggs and egg pods showed that C. robustus has tremendous variation from the other two studied species. Furthermore, there is a distinction in shape and size in both eggs and egg pods among the three selected species. From the study, it reveals that adult body size can also corelates to size of egg pods and number of eggs within the pod. Although there are morphometric differences among the studied acridids species, O. velox shows suitability for farming due to its voltinism and high egg pods retrieval under laboratory condition.